The Lisbon ranking for smart sustainable cities in Europe - Akande, Adeoluwa (2018)
Akande, A., Cabral, P., Gomes, P., & Casteleyn, S. (2019). The Lisbon ranking for smart sustainable cities in Europe. Sustainable Cities and Society, 44, 475-487. DOI: 10.1016/j.scs.2018.10.009